Composição de dívidas corporativas no Brasil: fatores que explicam a emissão de debêntures - Cruz, Fernando Baptista da (2010)
The purpose of the debt and the enterprise’s sector are important variables for the debate on corporate indebtedness composition in the context of the agency theory. The Brazilian empirical literature does not include those variables in its models. The aim of this study is to investigate if the purpose of the public debt and the enterprise’s sector have an influence on the financing source. In this context, it was used the LOGIT model in order to analyze these variables with others that were significant in past studies. The results imply that regulated sectors and resources allotted to the acquisition of equity participation increase the chance of choosing public debt. Furthermore, it was not found any evidence that a higher fixed assets to total assets ratio has an influence on the decision to issue a public debt.